Analisis Pembatalan Pesanan di Platform Shopee Menggunakan Seven Tools: Studi Kasus pada UMKM Puntang Coffee - Manthiq, Hanif; Pardian, Pandi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Although e-commerce makes it easier for businesses to expand their markets, this convenience allows buyers to easily cancel orders, disrupting MSME operations. This research aims to analyze the main causes of order cancellations at the Puntang Coffee store on the Shopee platform and to formulate control proposals. This study uses a qualitative case study method, with data analyzed descriptively via the Seven Tools approach. The Pareto analysis shows that the dominant causes of cancellation are "Incorrect Order Input" and "Payment Failure". Root cause analysis reveals that "Incorrect Order Input" stems from internal factors such as a lack of product content standardization and slow seller response due to limited human resources. Meanwhile, "Payment Failure" is rooted in unconvincing product content, the absence of a proactive intervention SOP from the seller, and unexpected costs during checkout. It is concluded that the main causes are a combination of controllable internal factors and difficult-to-change external factors, with a cancellation pattern peaking at 11:00-14:00. Therefore, it is recommended to implement a product content SOP, optimize customer service through scheduled responses, apply proactive interventions for payments, and increase cost transparency.